Ceo Publicity And Earning Management : Evidence From Malaysian Listed Companies - Goh, Jackie Chin Yong (Universiti Malaysia Sarawak, (UNIMAS), 2016)
In this research, the Google search volume index for a CEO's name and stock ticker are used to measure the CEO publicity, and examine the competing hypotheses on its effect on the earning management. Based on the analysis of the CEOs of 514 Malaysia listed companies from Bursa Malaysia between 2010 and 2014, the finding supports the former and shows that the CEOs with high publicity provoke a higher degree of earning management and manipulate the earnings performance of the companies. The findings are robust to other measures of earning management, and have important implications on both earning performance and investors. Further research is suggested in order to identify if the findings are similar for all the industry sectors.